Pengaruh Digitalisasi, Edukasi, dan Literasi Keuangan Syariah Terhadap Minat Investasi di Pasar Modal Syariah : Studi Kasus pada Generasi Milenial dan Gen Z di Kabupaten Pekalongan - Sandi Roy Erfangga; Moegiri Moegiri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the influence of digitalization, education, and Sharia financial literacy on investment interest in the Sharia capital market among the younger generation (Millennials and Generation Z) in the Pekalongan Regency area. A quantitative approach was employed with a sample of 48 respondents; data analysis involved IBM SPSS v27, classical assumption testing, and multiple linear regression. The results indicate that, individually, the variables of digitalization (X1), education (X2), and Sharia financial literacy (X3) have a positive and significant influence on investment interest (Y). Simultaneously, these variables digitalization (X1), education (X2), and Sharia financial literacy (X3) collectively exert a significant influence on the investment interest (Y) of Millennials and Generation Z in Pekalongan Regency. The study underscores the importance of facilitating online account opening, providing education through seminars, social media, and lectures, and ensuring an understanding of Sharia-compliant decisions to boost investor participation at the regional level..